Health Education on Interactive Ways to Prevent COVID-19 in Desa Mudalang Kabupaten Tanah Bumbu - Dina Rafidiyah (UMBanjarmasin, 2021)
Lack of public awareness in preventing Coronavirus has resulted in an increasing number of deaths and has a major impact on the welfare of the Indonesian people, which includes health. Therefore, the aim of this community service is to provide education to the community to better comply with the health program so as to improve community health in Desa Mudalang, Kabupaten Tanah Bumbu. The method of implementation consists of three stages, namely planning, implementation, and evaluation. Meanwhile, because of the COVID-19 safety protocol, we carry out education from house to house. The results of this community service show that the people of Desa Mudalang, Kabupaten Tanah Bumbu received the information we conveyed so as to increase compliance with the importance of health protocols during the COVID-19 pandemic. Even though there are some residents who are afraid to accept us because they think we want to ask for donations or some even think we want to give a COVID-19 vaccine.